PROBLEMATIKA KOMUNIKASI INTERPERSONAL PASANGAN USIA MUDA DALAM MEMPERTAHANKAN RUMAH TANGGA - Ekky Sri Wahyuni Sri Wahyuni (Program Studi Komunikasi dan Penyiaran Islam, Fakultas Dakwah dan Komunikasi, Universitas Islam Bunga Bangsa Cirebon, 2023)
Abstract : Communication is an important aspect of human life, especially in households, believed to have good feedback, communication often becomes the main problem that arises in household life. Interpersonal communication is a form of communication that must be applied to avoid problems in the household. The subjects in this study are young couples whose ages of marriage are not far apart. This study seeks to describe in depth what informants experienced through a phenomenological approach. The researcher uses two research data, namely primary and secondary data, where primary data comes from direct interviews with informants, while secondary data comes from journal articles, books, and the internet. The results of this study indicate that the process of interpersonal communication is very important, especially for young couples whose ages are not far apart to prevent problems in maintaining the household. Deduced from daily observations, it can be inferred that the informant has already implemented exemplary interpersonal communication skills. Henceforth, in order to establish a harmonious family unit, young couples are required to maintain cohesion and commitment towards their common objectives. Keywords: problematic, interpersonal communication and young couples.